Socialization of Effective Strategies for Choosing Study Programs and Scholarship Opportunities for Grade XII Students SMAN 2 Muaro Jambi, Indonesia - Mulyadi, Mulyadi; Muspawi, Mohammad; Nurmasah, Rahmat; Jamil, Helmun; Sholihah, Mar’atun (Advances in Community Services Research, 2025)
Purpose: This community service article aims to improve Grade XII students’ understanding of effective strategies for selecting study programs that match their interests, talents, abilities, and career aspirations, while also increasing their awareness of scholarship opportunities for higher education. Research Design and Methodology: The activity was conducted at SMAN 2 Muaro Jambi, Indonesia, involving 85 twelfth-grade students. It employed a descriptive community service approach through lectures, discussions, question-and-answer sessions, demonstrations, and questionnaires. Data were collected from participant engagement during the program and from post-activity evaluation of students’ understanding. Findings and Discussion: The results indicate that the activity was implemented successfully and received positive feedback from participants. Students demonstrated high enthusiasm, actively participated in discussions, and gained better understanding of study program selection, university admission pathways, and scholarship opportunities, including KIP Kuliah and university-based scholarships. Evaluation results indicated that 80% of participants understood the material presented. Implications: These findings suggest that structured outreach programs can effectively support students’ academic decision-making and motivate them to pursue higher education despite financial limitations. Continuous school-based guidance and wider dissemination of scholarship information are recommended to strengthen students’ readiness for post-secondary education.